Komparasi Kinerja Keuangan Sebelum dan Saat Pandemi - Gayuh Kurnia Wahidah; Ety Dwi Susanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The COVID-19 pandemic is affecting the economy. These economic activities affect the activities of companies or industries, one of which is commercial activities in the field of agricultural and food products, namely PT. Charoen Pokphand Tbk. This industry is an agribusiness that produces animal feed, day-old chicks (DOC), and ready-to-eat foods. This study was conducted during the closing period of 2019 and 2020 using quantitative research methods. The data collection process is an indirect study of the financial background of companies drawn from the Indonesian stock market. The objective of the study is to know the financial performance from the point of view of liquidity in the management of the company's finances in terms of short-term obligations, capital activities, and arrangement of the company in management or use of product support resources processes and measures of management effectiveness is expressed in the importance of profits generated, received on sale, or invested due to the occurrence of endemic diseases. Researchers use ratios to measure financial ratios, including debt-to-assets, debt-to-equity ratios, total asset turnover, return on assets, and net profit margin. Keywords: Covid-19, Financial Performance, Financial Ratio.